PENGEMBANGAN GAME BUBBLE MATCH SEBAGAI MEDIA PEMBELAJARAN PEMBAGIAN DALAM BENTUK PENGURANGAN BERULANG UNTUK SISWA KELAS 2 SD - ERVIANNA, ERNA (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to develop bubble match game as a medium of mathematics learning. This research focuses on the division material as a repeat reduction for grade 2 elementary students. Type of research used is Research and Development (RnD) model of ADDIE. The ADDIE development model has stages of Analysis, Design, Implementation and Evaluation. The bjects of this study are 2nd grade students of Elementary School Pangudi Luhur Ambarawa amounted to 37 students. Data collection techniques used are expert test / expert validation, test (multiple choice questions), non test (student response questionnaire and observation sheet). The effectiveness of this media was analyzed using Paired-Samples T Test conducted with SPSS program while the prevalence of media was analyzed using expert test. Media game bubble match proved valid based on validator’s judgment from media aspect that got score 4.1 with good category and from material aspect which got average score 3,9 with good category.